Advances in Array Optimization - Aksoy, Ertugrul (IntechOpen, 2020)
The need to develop technology and communication necessitates the design of flexible and high-capacity radiating systems in today's communication infrastructure. In this context, antenna arrays are the ideal solution and have been one of the priority research subjects of the science community dealing with electromagnetics from past to present. Optimization of an array may be performed in various ways such as the optimization of excitation, reflector structure, feed network, etc. depending on the array structure. This book is a collection of seven research studies focused on the optimization of array structures in classical phased array or time modulation, including radiator, reflector, feed network, and radiating element optimizations.